The KTKV model of the economics department of the Bank of Finland - Hannele Kuosmanen; Ilmo Pyyhtiä; Reijo Siiskonen (Bank of Finland, 1988)
This is a report on an updated version of the KTKV-model of Bank of Finland's Economics Department. The model was originally designed in the early 80's for the forecasting of short-term international economic developments. It is basically a world trade flow model, in which the main components of world trade flows are generated using trade weight matrices. Until recently, the demand side of the model has been entirely exogenous. For this version consumption and investment equations have been estimated. All other equations have been re-estimated and some technical equations for exchange rate and interest rate structures are introduced.
URN:NBN:fi:bof-201807301739
Keywords: 330